Christian Missions and Slavery - Jaap van Slageren (African Theological Journal for Church and Society, 2024)
While considerable research is available on the transatlantic slave trade and the cruelty suffered by African slaves in the Americas, less attention is given to the practices of slavery and forced labour in Africa. This article tells the story of slavery and forced labour in Cameroon. Douala kings kept slaves in slave villages and used their blood to sprinkle the grave of a deceased Douala prince. The German colonial government used Africans as forced labour to cultivate private plantations. The French government also coerced local Africans to produce food for the the troops fighting Nazism. The Christian missionaries and missions played a mixed role in countering and sustaining these power relations.